Implementasi Nilai-Nilai Tauhid dalam Dakwah Islamiyah di Era Digital - Alfadhilah, Jauharotina; Nurul Hidayah, Dwi; Fianur Laila, Lathifah (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2025)
The digital era offers transformative opportunities for Islamic da'wah (propagation) to reach diverse and global audiences efficiently and creatively. This study emphasizes tauhid (the oneness of Allah) as the core of Islamic teachings, exploring its significance, practical application, and relevance in the digital sphere. Key discussions include ethical guidelines rooted in tauhid for digital da'wah, challenges such as misinformation and audience saturation, and strategic methods to optimize tauhid-based content using innovative platforms. By analyzing successful approaches and addressing obstacles, this article provides actionable insights for maximizing the impact of digital da'wah in the modern technological landscape.